Symmetry in Single-Polarization Reflector Impulse Radiating Antennas - Baum, C.E. (Радиофизика и радиоастрономия, 2002)
There are various construction details for reflector impulse-radiating antennas (IRAs) which limit the achievement of the ideal performance characteristics. Symmetry planes are important for polarization purity in the direction of the main beam. This involves details of the feed cables, possible inclusion of a ground plane perpendicular to the ideal electric field, and location of perturbations in low-field regions. Another symmetry concerns the balancing of the low-frequency electric and magnetic dipoles by including special structures connected to the feed arms.